RUNX1/miR-582-5p Pathway Regulates the Tumor Progression in Clear Cell Renal Cell Carcinoma by Targeting COL5A1 - Xue, Jianxin; Zhu, Shenhao; Qi, Feng; Zhu, Kai; Cao, Pu; Yang, Jie; Wang, Zengjun (Frontiers in Oncology, 2021)
Recent evidences indicated that miRNAs played core role in the progression of clear cell renal cell carcinoma (ccRCC). However, its molecular mechanism in ccRCC is still remained unclear. The study was designed to identify the role and regulatory mechanism of miR-582-5p in ccRCC. In this study, the low expression level of miR-582-5p were detected by qRT-PCR in ccRCC patient tumor samples and ccRCC cell lines, respectively. The expression level of miR-582-5p was associated with tumor stage and metastasis. In vivo and in vitro experiments found miR-582-5p inhibit tumor growth via suppressing COL5A1 expression. Additionally, RUNX1 was identified as the negative regulator of miR-582-5p through database prediction and chromatin immunoprecipitation. Finally, the negative relation of RUNX1 and miR-582-5p was verified through rescue experiment both in vitro and in vivo. In summary, miR-582-5p, which was regulated by RUNX1, inhibited tumor growth and invasion by targeting COL5A1, indicating that miR-582-5p may act as a biomarker and that the RUNX1/miR-582-5p/COL5A1 axis could be a potential therapeutic target for ccRCC.